RBPJ Controls Development of Pathogenic Th17 Cells by Regulating IL-23 Receptor Expression - Gerd Meyer zu Horste; Chuan Wu; Chao Wang; Le Cong; Mathias Pawlak; Youjin Lee; Wassim Elyaman; Sheng Xiao; Aviv Regev; Vijay K. Kuchroo (Cell Reports, 2016)
Interleukin-17 (IL-17)-producing helper T cells (Th17 cells) play an important role in autoimmune diseases. However, not all Th17 cells induce tissue inflammation or autoimmunity. Th17 cells require IL-23 receptor (IL-23R) signaling to become pathogenic. The transcriptional mechanisms controlling the pathogenicity of Th17 cells and IL-23R expression are unknown. Here, we demonstrate that the canonical Notch signaling mediator RBPJ is a key driver of IL-23R expression. In the absence of RBPJ, Th17 cells fail to upregulate IL-23R, lack stability, and do not induce autoimmune tissue inflammation in vivo, whereas overexpression of IL-23R rescues this defect and promotes pathogenicity of RBPJ-deficient Th17 cells. RBPJ binds and trans-activates the Il23r promoter and induces IL-23R expression and represses anti-inflammatory IL-10 production in Th17 cells. We thus find that Notch signaling influences the development of pathogenic and non-pathogenic Th17 cells by reciprocally regulating IL-23R and IL-10 expression.